2021
DOI: 10.4103/jfmpc.jfmpc_1484_20
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and demographic characteristics of patients with coronavirus disease 2019 in Security Forces Hospital, Riyadh, Saudi Arabia

Abstract: Background: Corona virus disease (COVID-19) is a global pandemic public health problem which affected more than 5 million worldwide and caused more than 500,000 deaths. Disease presentations varied from a symptomatic or mild to severe illness which leads to death. Aim: The study describes the demographic and clinical characteristics patients with coronavirus disease 2019 (COVID-19) admitted to Security Forces Hospital in Riyadh, Saudi Arabia between 15 th … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“… 46.4 % (356/768) Al-Omari et al, 2020 [ 38 ] April 22, 2020 to May 21, 2020 Descriptive, cross-sectional study non-intensive care unit only) Dr. Sulaiman Al-Habib Medical Group's hospitals, As-Suwaidi, Rayan, Al-Takhassusi, Olaya and Al-Hammadi hospital, Riyadh, Saudi Arabia 10 % (41/401) Al Hayek et al, 2020b [ 6 ] May 2020 to July 2020 Retrospective study Prince Sultan Military Medical City, Riyadh, Saudi Arabia 12.6 % (920/7260) Alguwaihes et al, 2020 [ 27 ] May 2020 to July 2020 Retrospective study King Saud University Medical City -King Khaled University Hospital, Riyadh, Saudi Arabia 68.3 % (300/439) Sheshah et al, 2021 [ 43 ] May 1, 2020 to July 31, 2020 Retrospective study King Salman Hospital, Riyadh, Saudi Arabia. 45.7 % (137/300) Ghoraba et al, 2021 [ 39 ] 15th March to June 30, 2020. Descriptive, cross-sectional study Security Forces Hospital, Riyadh, Saudi Arabia 21.8 % (123/566) Talib et al, 2021 [ 37 ] March 1, 2020 to June 30, 2020.…”
Section: Why Diabetes Is Important?mentioning
confidence: 99%
See 1 more Smart Citation
“… 46.4 % (356/768) Al-Omari et al, 2020 [ 38 ] April 22, 2020 to May 21, 2020 Descriptive, cross-sectional study non-intensive care unit only) Dr. Sulaiman Al-Habib Medical Group's hospitals, As-Suwaidi, Rayan, Al-Takhassusi, Olaya and Al-Hammadi hospital, Riyadh, Saudi Arabia 10 % (41/401) Al Hayek et al, 2020b [ 6 ] May 2020 to July 2020 Retrospective study Prince Sultan Military Medical City, Riyadh, Saudi Arabia 12.6 % (920/7260) Alguwaihes et al, 2020 [ 27 ] May 2020 to July 2020 Retrospective study King Saud University Medical City -King Khaled University Hospital, Riyadh, Saudi Arabia 68.3 % (300/439) Sheshah et al, 2021 [ 43 ] May 1, 2020 to July 31, 2020 Retrospective study King Salman Hospital, Riyadh, Saudi Arabia. 45.7 % (137/300) Ghoraba et al, 2021 [ 39 ] 15th March to June 30, 2020. Descriptive, cross-sectional study Security Forces Hospital, Riyadh, Saudi Arabia 21.8 % (123/566) Talib et al, 2021 [ 37 ] March 1, 2020 to June 30, 2020.…”
Section: Why Diabetes Is Important?mentioning
confidence: 99%
“…Further, another study done with 300 adult patients carrying confirmed SARS-CoV2 infection and hospitalized at King Salman Hospital from May 1 to July 31, 2020, showed T2D as the most typical comorbidity in 45.7 % of those affected with COVID-19 disease [ 15 ]. A study conducted among 566 patients at Security Forces Hospital in Riyadh, Saudi Arabia, between March 15 and June 30, 2020, showed that the most common comorbidity was diabetes (21.8 %; 123/566) [ 39 ]. It is noteworthy that the Ministry of Health (MOH) in Saudi Arabia confirmed that approximately 50 % of the COVID-related deaths among the critical cases present in an ICU were from among patients experiencing chronic diseases such as diabetes [ 40 ].…”
Section: Why Diabetes Is Important?mentioning
confidence: 99%
“…and 3.63 times higher among deaths 29 . Individuals with comorbidities were the majority among those admitted in March 2020 to a hospital in Saudi Arabia 30 . Although comorbidities increase the chances of worsening and death of the disease, our study only cardiovascular diseases and diabetes mellitus showed differences in whether or not to perform the molecular test for COVID-19.…”
Section: Discussionmentioning
confidence: 99%